2008
DOI: 10.1007/s12237-008-9053-8
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Abundance and Domoic Acid Analysis of the Toxic Diatom Genus Pseudo-nitzschia from the Chesapeake Bay

Abstract: Very little research has been conducted on midAtlantic estuarine populations of the diatom Pseudonitzschia despite recent evidence of toxicity in regional isolates. We collected field samples from the Chesapeake Bay region from 2002 to 2007 for Pseudo-nitzschia enumeration and toxin analysis. Abundances of Pseudonitzschia were highest in the winter and spring at ∼10 3 cells ml −1 . Domoic acid (DA) was detectable in 42% of samples tested, but concentrations were generally low, ranging from 0 to 1,037 pg DA ml … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 23 publications
4
26
0
Order By: Relevance
“…Although Pseudo-nitzschia spp. are usually observed close to the mouth of estuaries (SPATHARIS et al, 2007;STOECKER, 2008), they can also occur at lower salinities, as was the case in several areas of Chesapeake Bay with salinities up to 6 (THESSEN; STOECKER, 2008) and in the present study, where they were observed at salinities as low as 14.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Although Pseudo-nitzschia spp. are usually observed close to the mouth of estuaries (SPATHARIS et al, 2007;STOECKER, 2008), they can also occur at lower salinities, as was the case in several areas of Chesapeake Bay with salinities up to 6 (THESSEN; STOECKER, 2008) and in the present study, where they were observed at salinities as low as 14.…”
Section: Resultssupporting
confidence: 77%
“…The species found in this study are regarded as eurythermic STOECKER, 2008;QUIJANO-SCHEGGIA et al, 2008;LIEFER et al, 2009;ANDERSON et al, 2010;LJUBESIC et al, 2011). The euryhaline and eurythermic features of both species pose serious potential implications for aquaculture.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…In any case, there is a great inter-and intraspecific variability in DA cell quotas measured among Pseudonitzschia strains isolated into culture from different regions of the world (Trainer et al, 2012). In addition, highly variable cell quotas are typically found among natural Pseudo-nitzschia populations (Schnetzer et al, 2007;Thessen and Stoecker, 2008), but some of this apparent variability may be attributable to DA estimates based upon total cell densities of Pseudo-nitzschia, which usually includes several co-occurring species.…”
Section: Introductionmentioning
confidence: 99%
“…Low Pseudo-nitzschia abundances and low, irregular DA concentrations may partially explain the lack of documented toxic events in the Chesapeake Bay (Thessen and Stoecker, 2008).…”
mentioning
confidence: 99%